Probing Location of Anti‐TB Drugs Loaded in Brij 96 Microemulsions Using Thermoanalytical and Photophysical Approach. Issue 3 (14th January 2014) - Kaur, Gurpreet; Mehta, Surinder K.
<x xml:space="preserve">Abstract</x> The aim of this work is to monitor the changes in microstructure in nonionic Brij 96 microemulsions and to locate the solubilization loci of antituberculosis drugs (of variable solubility using photophysical and thermoanalytical properties. Using properties such as spectral shift, Stroke's shift, and anisotropy for two dyes, that is, Nile red (NR) and tris(2, 2′‐bipyridine)ruthenium(II) dichloride (RC), the structure of microemulsions has been investigated. With the help of spectral and deconvoluted analysis, it has been seen that rifampicin (RIF) shows a strong interaction with NR and isoniazid (INH) and pyrazinamide (PZA) with RC. It has been concluded that RIF molecules are mainly present at the interface toward oil side and INH toward hydrophilic side, whereas PZA remains in free water. The findings have been correlated with aqueous solubility drugs and partition coefficients. Differential scanning calorimetry elucidates the state of water in microheterogeneous environment and variation of different states, that is, free, bound, interphasal, and nonfreezable water with dilution. In addition, it confirmed the stability and location of the drugs in the prepared Brij 96 microemulsion formulations. A good agreement between both the studies has been achieved. These findings will help in elucidating the drug delivery properties of anti‐TB drugs‐loaded microemulsion formulations in future. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:937–944, 2014